Designing low viscosity furan epoxy polymers of the materials for construction industry - Rassokha, A.; Cherkashina, A. (Технологический центр, 2016)
The materials are designed and the properties are studied of the low viscosity furanepoxy reactive oligomers, structured by amine complex curing agents for the use as injection systems during the repairing and recovery construction work. A wide range of the amine containing structuring agents that have industrial potential and ensure a high degree of conversion was analyzed. This makes it possible to form the rational structure of furan epoxy polymers, which is due to the application of optimal parameters of structuring (temperature, concentration of ingredients, time and others) during the formation of the polymeric composition systems for construction purposes. The structure topological parameters were studied (traditional topological criterion of Wiener and others) and certain parameters of reactivity (structural functionality, formal unlimitedness, the index of distribution of electron density on the atoms of molecule, etc.) parent substances (monomers) during obtaining furan epoxy materials. The knowledge of this set of characteristics makes it possible to purposefully regulate structure and properties of the designed low viscosity injection furanepoxy polymeric materials. The deformation strength, adhesive, sorption, technological properties of the proposed low viscosity injection furan epoxy polymers for construction purposes were explored. As a result of the optimal combination of the set of structural topological parameters and technological factors, the high level of physical mechanical, adhesive properties, water resistance of the designed composite materials is ensured. The development of composite polymeric systems was accomplished with the use of the “green chemistry” principles.

Розроблено склади і досліджені властивості низьков'язких фурано-епоксидних олігомерів, які структуровані амінними затверджувачами для використання при ремонтно-відновлювальних будівельних роботах. Визначено діапазон оптимальних параметрів структурування полімерних систем. Досліджені структурно-топологічні параметри і реакційна здатність вихідних речовин при отриманні фурано-епоксидних матеріалів. Проведено дослідження міцностних, адгезійних, сорбційних властивостей розроблених низьков'язких фурано-епоксидних полімерів.
Keywords: furanepoxy reactive oligomer; amine containing curing agent; strength; sorption properties; adhesive strength; low viscosity injection system; construction industry; фурано-епоксидні олігомери; аміновмісткі затверджувачі; адгезійні властивості; сорбційні властивості; низьков'язка система